Cardiovascular safety of mometasone/indacaterol and mometasone/indacaterol/glycopyrronium once-daily fixed-dose combinations in asthma: pooled analysis of phase 3 trials. (April 2021) - Scosyrev, Emil; van Zyl-Smit, Richard; Kerstjens, Huib; Gessner, Christian; Kornmann, Oliver; Jain, Devendra; Aubrun, Elodie; D'Andrea, Peter; Hosoe, Motoi; Pethe, Abhijit; Brittain, Dominic
Abstract: Objective: To evaluate cardiovascular safety of two new inhaled fixed-dose combinations for treatment of asthma: (i) the inhaled corticosteroid/long-acting beta2-agonist (ICS/LABA) mometasone furoate/indacaterol acetate (MF/IND), (ii) the ICS/LABA/long-acting muscarinic antagonist (LAMA) MF/IND/glycopyrronium bromide (GLY). Methods: Patient-level data were pooled from four randomized trials, including 52-week studies PALLADIUM (n = 2216) and IRIDIUM (n = 3092), 24-week study ARGON (n = 1426), and 12-week study QUARTZ (n = 802). Cardio-/cerebrovascular (CCV) event frequencies were examined in the following comparisons: (1) LABA effect: pooled-dose MF/IND vs. pooled-dose MF; (2) LAMA effect: pooled-dose MF/IND/GLY vs. pooled-dose MF/IND; (3) ICS-dose effects: (a) high-dose MF/IND vs. medium-dose MF/IND, (b) high-dose MF/IND/GLY vs. medium-dose MF/IND/GLY; (4) intra-class effects: (a) high-dose MF/IND vs. Fluticasone/Salmeterol (F/S), (b) high-dose MF/IND/GLY vs. F/S + Tiotropium (TIO). Risk estimates (percentage of patients with ≥1 CCV event) and risk differences (RDs) with 95% confidence intervals (CIs) were calculated for each comparison. Results: The frequency of CCV events was low, without notable differences between comparison groups. Risk estimates and corresponding RDs (95% CIs) were as follows: (1) pooled-dose MF/IND = 2.35%, pooled-dose MF = 2.18%, RD = 0.17% (−1.00%, 1.34%); (2) pooled-dose MF/IND/GLY = 3.65%, pooled-dose MF/IND = 3.77%, RD = −0.12% (−1.63%, 1.39%); (3a) high-dose MF/IND = 3.69%, medium-dose MF/IND = 3.35%, RD = 0.34% (−1.25%, 1.94%); (3b) high-dose MF/IND/GLY = 2.84%, medium-dose MF/IND/GLY = 2.02%, RD = 0.82% (−0.49%, 2.13%); (4a) high-dose MF/IND = 3.69%, F/S = 2.82%, RD = 0.87% (−0.66%, 2.40%); (4b) high-dose MF/IND/GLY = 1.26%, F/S + TIO = 1.05%, RD = 0.21% (−1.26%, 1.68%). Conclusions: There was no evidence of increased cardiovascular risk attributable to the addition of IND to MF or addition of GLY to MF/IND. Similarly, no evidence of increased cardiovascular risk was observed with an increase in the ICS-dose or relative to F/S ± TIO.